From the Terminology Based on Eponyms in Surgery, to the International Anatomical Terminology: A Great Abyss that Can Be Avoided (International Journal of Medical and Surgical Sciences, 2014)
In surgical sciences the use of language based on morphological eponyms, which have no descriptive or informative value of an anatomical structure is common, perhaps because these professionals know or have forgotten that there is a anatomical terminology that seeks to unify communication and facilitate learning. Eradicating the eponymous form the surgical sciences is a difficult task, because their use is still reinforced in textbooks, scientific papers and conferences, among others, thus promoting the use of a chaotic and confusing language. Therefore, the need arises to strengthen the use of Anatomical Terminology in new generations of surgeons, as clearer and more accurate communication will be achieved between health professionals and will also facilitate the teaching-learning process.